Vascularized Lymph Node Transfer for the Treatment of Posttraumatic Lower Extremity Lymphedema: A Preliminary Report - Pedro Ciudad (Indian Journal of Plastic Surgery, 2022)
Background Posttraumatic lymphedema develops more frequently than expected and reports on its management are scarce in the literature. We aimed to report the clinical outcomes of a case series of posttraumatic lymphedema patients treated with different vascularized lymph node transfers (VLNTs). Patients and Methods Five patients with secondary posttraumatic lower limb lymphedema treated with VLNT were included in this report. The groin-VLNT (n = 1), supraclavicular-VLNT (n = 2), and gastroepiploic-VLNT (n = 2) were implemented. The average flap area was 69.8 cm2. Patients underwent postoperative complex decompressive therapy for an average of 10.0 months. Results The average mean circumference reduction rate was 24.4% (range, 10.2–37.6%). Postsurgical reduction in the number of infection episodes per year was observed in all patients. The mean follow-up was 34.2 months. Conclusions VLNT is a promising surgical treatment for posttraumatic lymphedema patients. In our report, VLNT has demonstrated to reduce the volume and number of infections per year in posttraumatic lymphedema.